Pengaruh Kepercayaan, Persepsi Kemudahan, dan Kualitas Informasi terhadap E Filling dalam Perpajakan - Darma, Sapta Setia; Ariwibowo, Muhammad Eko; Septanta, Rananda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to examine the factors that influence the use of E-filing applications, namely Trust, Perception of Ease, and Information Quality on the use of E-fillingThe population in this study are all corporate taxpayers registered at the Cikupa Primary Tax Service Office, Tangerang. The sampling technique used in determining the sample in this study was incidental sampling (convenience sampling). This technique is one of the Non-Probability Sampling techniques where the sampling technique is based on coincidence, ie anyone who accidentally meets a researcher can be used as a sample if it is felt that the person who happened to be found is suitable as a data source. The data used are primary data in the form of the number of individual taxpayers.Based on the results of the analysis that has been done, this study shows that partial trust has no significant effect on the use of E-filing, Perception of Efficiency partially has a significant effect on the use of E-filing, Information Quality partially has no significant effect on the use of e-filing systems, and Trust, Perception of Ease and Quality of Information simultaneously have a significant effect on the use of Tax E-filing.